Indigenous practices for cultivation of fruit plants in Kampung Dukuh, West Java, Indonesia - Anggraeni, Anisa; Hidayati, Eisya Hanina; Yuniati, Ratna; Kien-Thai, Yong; Sujarwo, Wawan (Ethnobotany Research and Applications, 2024)
Background: Fruit is underrepresented as a source of nutrition owing to high production challenges and a lack of successful domesticating techniques. However, this issue can be addressed if an effective indigenous practice can be identified, and then the techniques can be promoted and shared with other communities. This research aims to document: (1) the landscape and land classification in Kampung Dukuh, (2) the fruit plants found in Kampung Dukuh, and (3) the cultivation technique practiced by indigenous people. Methods: The research was conducted through field observations at 162 sites within the village and in-depth interviews with 30 informants selected using the purposive sampling method. Data were analyzed using Miles and Huberman Models. Results: (1) Indigenous people have traditional practices in understanding their living environment and have divided the living area into five zones, viz., cover land, deposit land, arable land, forbidden land, and reserve land (2) a high fruit plant diversity of 587 plants belonging to 90 species and 38 families were present in Kampung Dukuh. The most dominant family is Moraceae (13.33%), followed by Anacardiaceae (10%) and Rutaceae (8.89%) (3) The fruit plant cultivation technique involves a series of processes from site preparation, planting, tree caring, and fruit harvesting. Conclusions: Indigenous people divide their land into five zones and cultivate 90 species of fruit plants. Their cultivation techniques, from site preparation to harvesting, underscore the value of indigenous knowledge and highlight the area’s rich fruit plant diversity. These practices offer valuable insights for sustainable fruit cultivation in similar contexts. Keywords: traditional methods, cultivation technique, indigenous people